CRIMINAL LIABILITY FOR MISUSE OF ARTIFICIAL INTELLIGENCE (AI) IN DEEPFAKE CRIMES - JANDRIE SEMBIRING; SUNNY UMMUL FIRDAUS (CV KULTURA DIGITAL MEDIA, 2025)
Artificial Intelligence (AI) has brought significant innovations in various fields, but it has also created new challenges in the realm of criminal law. One of the negative implications of AI is its misuse in the deepfakes crimes, a media manipulation technology that can create video, audio, or image content that appears authentic but is fake. Crimes involving deepfakes can include blackmail, spreading fake news, defamation, and privacy violations. This paper discusses the criminal liability for the use of AI in deepfake crimes, highlighting relevant legal aspects, including who can be held liable, the AI creator, the technology user, or other related parties. This article examines the criminal liability of AI used to commit deepfake abuse. This study analyzes existing regulations, including the Electronic Information and Transactions Law (UU ITE), as well as the role of law enforcement agencies in combating deepfake crimes. In addition, this study also identifies challenges faced in the law enforcement process, such as limited resources, lack of coordination between agencies, and gaps in understanding technology among law enforcement officers. The results of the study show that there is a legal and regulatory vacuum governing Artificial Intelligence and Deepfake Crimes, although there are regulations on Information and Electronic Transactions (ITE) but they have not been able to resolve the problem of deepfake crimes that are increasingly occurring in Indonesia. significant progress in the legal framework and policies related to cyber crime, there are still many obstacles that reduce the effectiveness of law enforcement. Therefore, efforts are needed to strengthen the ongoing regulatory side to strengthen the capacity of law enforcement institutions, increase international cooperation, and update regulations to be in line with technological developments. Thus, it is hoped that law enforcement against deepfake crimes that utilize artificial intelligence in electronic transactions in Indonesia can be more optimal in protecting the public from misuse of AI and deepfake crimes..